THE EFFECT OF TAX KNOWLEDGE AND TAX SANCTIONS ON TAXPAYER COMPLIANCE OF PERSONAL ENTREPRENEURS IN THE STATIONERY SECTOR - Michele Sudiarto; Yopy Junianto (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2023)
Tax is one of the national incomes owned by Indonesia. Tax will later be used to build and develop the existing infrastructure in Indonesia. Tax is an obligation for citizens who are registered as individual taxpayers. One way to be a good citizen is to pay taxes on time. However, there are still many taxpayers who have not complied with their tax obligations. There are several factors that affect the compliance of individual taxpayers, such as knowledge of taxation and tax sanctions. The purpose of this study is to determine the effect of knowledge of taxation and tax sanctions on individual taxpayer compliance among stationery entrepreneurs. The population in this study are stationery entrepreneurs on the island of Java. The sample taken is 50 respondents through a questionnaire. The research method used is multiple linear regression. The results of the study indicate that tax knowledge does not affect taxpayer compliance, while tax sanctions affect taxpayer compliance.